POSSIBLE MECHANISM OF POSTHUMOUS TRANSFORMATION OF CALCIUM PHOSPHATE SHELLS OF OLD INARTICULATE BRACHIOPODS - Ushatinskaya G.T.; Zezina O.N. (My University, 1988)
The posthumous phosphatization of the organic part of shells was produced by the mineral component of the shells themselves, that is, there occurred a posthumous redistribution of the calcium phosphate itself, which became the secondary mineralizer of the organic matter of the shell. This interpretation explains the hollow spaces between shell layers in the old acrotretids: the inorganic matter was expended in the mineralization of the organic matter, and the double structure of the layers (except for the outermost one) means that the phosphatization of each organic layer proceeded from both sides (in the outer layer this process could run only from the inside). The radially acicular structure of the columellae can be explained in exactly the same way. The spherulitic structure of the columellae in Eothele could have been produced by later recrystallization of the phosphatic material.